2010
DOI: 10.1007/s10856-010-4138-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of superhydrophilic microrough titanium implant surfaces by alkali treatment

Abstract: A new strategy to render intrinsically hydrophobic microrough titanium implant surfaces superhydrophilic is reported, which is based on a rapid treatment with diluted aqueous sodium hydroxide solutions. The physicochemical characterization and protein interaction of the resulting superhydrophilic implant surfaces are presented. The superhydrophilicity of alkali treated microrough titanium substrates was mainly attributed to deprotonation and ion exchange processes in combination with a strong enhancement of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 44 publications
5
82
0
Order By: Relevance
“…The correlation of histological and micro-computed tomographic data for the analysis of BIC and bone volume has been analysed in an earlier study applying synchrotron radiation (Bernhardt et al, 2012). The conditioning by hydroxide ions influences surface charge, hydrophilicity and the homogeneity of the initial protein layer (Tugulu et al, 2010). Various animal studies utilising non-osteoporotic conditions have analysed mechanics and histomorphometry of such conditioned implants, and demonstrated increased bone formation and removal torque values indicating improved osseointegration (Ferguson et al, 2006;Calvo-Guirado et al, 2010;Stadlinger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of histological and micro-computed tomographic data for the analysis of BIC and bone volume has been analysed in an earlier study applying synchrotron radiation (Bernhardt et al, 2012). The conditioning by hydroxide ions influences surface charge, hydrophilicity and the homogeneity of the initial protein layer (Tugulu et al, 2010). Various animal studies utilising non-osteoporotic conditions have analysed mechanics and histomorphometry of such conditioned implants, and demonstrated increased bone formation and removal torque values indicating improved osseointegration (Ferguson et al, 2006;Calvo-Guirado et al, 2010;Stadlinger et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Disk-shaped Ti surfaces of 15 mm in diameter and 2 mm thickness composed of titanium grade 4 (Dynamet Incorporated, Washington, PA, USA) were prepared, sandblasted, acid-etched (SBA) and alkali-treated when necessary as previously described (Tugulu et al, 2010). Alkali treatment was performed by sonicating the Ti surfaces in 0.05 M aqueous NaOH for 30 s at room temperature.…”
Section: Preparation Of Titanium Surfacesmentioning
confidence: 99%
“…Preliminary studies demonstrated stronger osseointegrative potential of alkali-treated microrough SBA Ti implants in vivo (Calvo-Guirado et al, 2010;Stadlinger et al, 2009). Surface analysis indicated that superhydrophilicity of alkali-treated microrough SBA Ti surfaces might at least partly be attributed to deprotonation and ion exchange of hydroxyl-groups on the TiO 2 -x surfaces increasing the ionic character and the net negative surface charge (Tugulu et al, 2010). Also, Kokubo and colleagues investigated the effect of alkali-and heat-treatment on Tantalum surfaces' osseointegration and showed that bone bonding to plates implanted into rabbit tibiae was greater for heat-and alkalitreated tantalum implants compared to native ones.…”
Section: Introductionmentioning
confidence: 99%
“…This layer has been demonstrated to be beneficial for the rapid nucleation of bone-like mineralization during the period of immersion in simulated body fl uid (SBF) 27,28) . Some in vitro studies have demonstrated that alkali-treated titanium could induce more rapid apatite formation on the surface than the untreated pure titanium surface 29,30) . Our previous study showed that diff erent concentrations of NaOH solution could produce diff erent surface nanotopographies and that the osteogenic activities on these surface nanotopographies were also different 13) .…”
Section: Discussionmentioning
confidence: 99%